Evolution of brightness and magnetic features of young solar-type stars – I. The young G star HIP 89829. Issue 3 (29th September 2021) - Perugini, G M; Marsden, S C; Waite, I A; Jeffers, S V; Piskunov, N; Shaw, N; Burton, D M; Mengel, M W; Hughes, J E; Hébrard, E M
ABSTRACT: The evolution in latitude of sunspots is a key feature of the cyclic solar dynamo. Here, we present the results of a spectroscopic and spectropolarimetric monitoring campaign on the young (∼20 Myr old) early G star HIP 89829, in order to investigate potential evolution in the distribution of the star's spots and magnetic features. Our analysis of this G5V star spans eight epochs, from June 2010 to August 2015. The techniques of Doppler imaging and Zeeman–Doppler imaging were used to create brightness maps for each epoch and magnetic maps for two epochs. The brightness images show the star to have stable spot features with two main spot latitudes – a polar spot, often seen on young rapidly rotating stars such as this, and another highly unusual group of large spot features around the 20° and 30° latitudes. These lower spot latitudes appear to be rather stable over the 5 yr of observations. We included a solar-type differential rotation law into the imaging process and measured near-solid-body rotation for epochs where sufficient data exist for this analysis. The magnetic features show a dominant poloidal and a weaker toroidal magnetic field for both Stokes V epochs, which is unusual for a star with a rapid rotation period of 0.57 d. We conclude that HIP 89829 is an active young solar-type star with long-lived spots and near-solid-body rotation.